Sexually transmitted infections among high-risk populations that use treatment as prevention or pre-exposure prophylaxis: a protocol for a systematic review - Makella Coudray; Sandra Kiplagat; Franklin Saumell (BMJ Open)
Background Among men who have sex with men, pre-exposure prophylaxis (PrEP) reduces the risk of HIV by 95%. Based on the documented benefits, the Centre for Disease Control and Prevention has recommended PrEP as a prevention method for high-risk groups. Moreover, for those HIV-infected individuals, antiretroviral therapy has been shown to serve as both as a treatment and prevention method for HIV.Methods and analysis This systematic review protocol was reported according to the Preferred Reporting Items for Systematic reviews and Analyses (PRISMA) P framework. Medline (1980–present), Embase (1980–present), CINAHL (1980–present), Cochrane Central Register of Controlled Trials and clinicaltrials.gov will be used to identify relevant articles based on a piloted search strategy. Peer-reviewed observational and experimental studies will be included. A narrative style will be used to describe descriptive data. A meta-analysis will be conducted if heterogeneity is not significant.Ethics and dissemination Recent evidence suggests that there is an increased risk of sexually transmitted infections (STIs) among high-risk persons that use PrEP. Furthermore, there is a paucity of data on the relationship of treatment as prevention and incidence of STIs. The findings of this review will assess this emerging public health phenomenon and serve to inform future public health policy. No formal ethical review is required for this protocol. All findings will be published in a peer reviewed journal.PROTOCOL registration number CRD42019128720.